Dumbbell-Shaped Epidural Cavernous Hemangioma in the Thoracic Spine Mimicking Schwannoma. Issue 7 (October 2016) - Wang, Shantao; Wang, Mingwei; Wang, Fuchao; Yuan, Xunhui; Xiao, Hang; Bai, Yun'an; Liu, Fucun
Abstract : Abstract: Dumbbell-shaped epidural cavernous hemangiomas (CHs) are extremely rare, and they are easily misdiagnosed as spinal schwannomas. Herein, the authors report 1 rare case of dumbbell-shaped epidural CH in the thoracic spine. To the best of our knowledge, only a few cases of dumbbell-shaped epidural CHs in thoracic spine have been reported. Furthermore, the clinical characteristics and treatments for spinal epidural CHs were investigated and reviewed.